PERBEDAAN TOPICAL FLUORIDE APPLICATION DAN FISSURE SEALANT DALAM MENCEGAH KARIES PADAGIGI MOLAR SATU - Pawarti Pawarti; Fathiah Fathiah (Jurnal Vokasi Kesehatan, 2017)
Abstract: Topical Fluoride Application And Fissure Sealant To Prevent Dental Caries Permanent First Molars. Anatomy pits and fissures of teeth are caries initiation vulnerable areas of the permanent molars that grow at the age of 6 years where children can not perform oral hygiene. Caries prevention can be done by closing the pits and fissures or application of fluoride (topical fluoride application) on the surface of the teeth. The purpose of this study was to analyze the difference fissure sealants and topical application of fluoride to prevent dental caries of first permanent molars. This study was a quasi-experimental study with time series, a sample was taken by purposive 117-second grade students of SDN District of North Pontianak. Data were analyzed using t-test. The result showed that fissure sealant more effective in caries prevention of first permanent molar than topical fluoride application where there were none caries teeth after and month fissure sealant, 25% sealant partially off and 11% fully off. Teeth that have done fluoride after 6 months of 3.9% of dental caries, the eighth month of 5.4% of dental caries. There was a significant difference between the effectiveness of fissure sealants with topical application of fluoride to prevent dental caries in first permanent molars p-value < 0.05, after 6-month p-value: 0.004 and after 8-month p-value: 0.001.